Mind, Metaphor, and Emotion in Euripides (Hippolytus) and Seneca (Phaedra) - Cairns, Douglas (2015)
Metaphor is crucial in the formation of concepts in general and of emotion and other psychological concepts in particular. Metaphors drawn from our experience as embodied beings in the world – with a particular physiology, a particular physical orientation, at home in particular natural and social environments – are fundamental in making things that might otherwise be difficult to think and talk about (such as subjective psychological experience) easier to think and talk about, by seeing them in terms of more basic, concrete, physical, and visible phenomena. This paper will pursue this general issue in an overview of emotion metaphor in Euripides’ Hippolytus and Seneca’s Phaedra – two versions of the same myth, and in some respects similar plays. Analysis of the relevant clusters and their thematic significance in each case will help corroborate Lakoff and Turner’s thesis on the continuity between (a) the background conceptual metaphors of everyday life and (b) the developed metaphors of poets and other literary artists (More than Cool Reason: A Field Guide to Poetic Metaphor, Chicago 1989). The worlds of both plays are worlds of metaphor. In both, the associative, symbolic world that the characters inhabit is also an intertextual one – it is through familiarity with cult, myth, narrative, poetry, and drama that audiences and readers know how to read its signs. In that respect, at least, though the basic dynamics of imagery are continuous with those of everyday thought and language, poetry has resources that differ somewhat from those of everyday speech.